A STUDY OF AETIOLOGICAL FACTORS OF HYPERTENSION IN HOSPITALIZED PATIENTS FROM RURAL AREAS OF ABBOTTABAD - Saeed, A.K.; Hussain, M.; Rashid, A.; Nawaz, S. (Journal of Ayub Medical College Abbottabad, 1989)
Abstract: Two hundred and fifty proven hypertensive patients from rural areas of Abbottabad were selected for this study. The study was conducted at Civil Teaching Hospital, Abbottabad. This study was conducted with the purpose to establish the relationship of hypertension with age, sex, body weight, tobacco addiction, literacy rate, serum cholesterol and kidney functions. Only 89 cases (35.6%) were traced to have some apparent cause of hypertension. The aetiology of hypertension in rest of the patients (64.4%) was unknown.